Generation of site-dependent earthquake ground motion parameters - Maskey, Prem Nath (Nepalese Journal of Engineering, 2005)
The generation of ground motion parameters, in the form of time histories, power spectral density functions or response spectra, specific to a site in a probabilistic format could result into an improved method of design. In the absence of enough earthquake records for a site, generation of site-dependent earthquake ground motions is the best alternative. A probabilistic method to simulate the seismic ground motion parameters specific to sites lying in earthquake prone region with a limited earthquake records is presented. Seismic hazard curves indicating the seismicity of a site and risk consistent spectral shapes and corresponding power spectral density functions are obtained using empirical relationships, and ground acceleration time histories are simulated using Monte Carlo technique. One dimensional wave propagation analysis, considering both linear and nonlinear behavior of soil overlying the bedrock is carried out to obtain the free field hazard curves and the ground motion parameters. The method is applied in generation of site-dependent ground motion parameters for three sites of Bhaktapur City of Kathmandu Valley. Major finding of the study shows that the free field hazard curves and the ground motion parameters vary from site to site, and are significantly influenced by the overlying soil characteristics of specific sites. Keywords: ground motion parameters, hazard curve, time history, response spectrum, power spectral density function, soil amplification Nepalese Journal of Engineering Vol.1(1) 2005 pp.84-91